Cycle-supermagic labeling for some families of graphs - Asif, Muhammad; Ali, Gohar; Numan, Muhammad; Semaničová-Feñovčiková, Andrea (Utilitas Mathematica, 2017)
A simple graph G = (V(G), E(G)) admits a cycle-covering if every edge in E belongs to at least one subgraph of G isomorphic to a given cycle C. The graph G is C-magic if there exists a total labeling f: V(G) ∩ E(G) -; {1,2,..., |V(G)| + |E(G)|} such that for every subgraph H' = (V(H'),E(H')) of G isomorphic to C, the sum σ v(H') f(v) + ) f(e)is instant. When (f(v)) : v ϵ V(G)} = {1,2,..., |V(G)|} then G is said to be C-supermagic. In the present paper, we investigate the cycle-supermagic behavior of disjoint union of graphs. © 2015 Utilitas Mathematics.